Bio-corrosion of Carbon Steel by Sulfate Reducing Bacteria Consortium In Oil and Gas Pipelines - A., Abu Bakar; M. K. F., Mohd Ali; N., Md Noor; N., Yahaya; M., Ismail; Arman, Abdullah (Faculty Mechanical Engineering, UMP, 2017)
This research is aimed to give an overview of the impact of bio-corrosion on carbon steel grade API 5L X-70 immersed in growth medium and exposed to SRB consortium. Simulation of anaerobic corrosion conditions was carried out in a laboratory for 28 days. Raw crude oil gathered from the Baram Delta Operation Terminal was cultured in broth number 1249 (Modified Barr’s Medium) to study the effect of bacteria growth upon metal loss. Carbon steel coupons grade X70 were cut to approximately 10mm x 20mm x 5mm and immersed in the cultured broth. During the experiment, the planktonic SRB were enumerated using a counting chamber (direct cell count method) under the electronic microscope at 200x magnification. Results indicated that the optimum pH and temperature for the respected SRB consortium genes were 8.5 and 37 °C, respectively. Metal loss of the corrosion specimen was measured and recorded after retrieval from the immersion period in the medium on a weekly basis prior to SRB inoculation for further analysis. The metal loss values supported that SRB activity can increase the metal loss of carbon steel against time of exposure. Additionally, the FESEM image showed the biofilm formations on the corrosion specimen. Thus, the results could conclude that biocorrosion caused by particular local SRB consortium can be considered as a threat to carbon steel pipelines. Besides, the effect of SRB activity and response towards metallic materials in a dynamic environment is an interesting topic to be studied upon in the future.